Morfologia e função tireoideanas na deficiência isolada de hormônio do crescimento - Alcântara, Marta Regina Silva de (2005)
There are complex relationships between GH system and hypothalamic-pituitarythyroid axis. Thyroid hormones play a fundamental role in the initiation and maintenance of somatic growth and are important in the regulation of several growth factors. The relationship between goiter and acromegaly is well known, but the unique study of thyroid volume in the growth hormone deficiency has shown reduced thyroid volume in hypopituity patients. The aim of this study was to asses the morphology and thyroid function in adults patients with isolated growth homone deficiency (IGHD) due to a mutation in the receptor of growth hormone releasing hormone (GHRH) of Itabaianinha. MATERIAL AND METHODS: 3 groups were studied: Group 1 - 24 individuals with IGHD ( MT/MT; 9M/15F, 43,7±15,8anos); Group 2 18 individuals heterozygous (WT/MT; 8M/10F, 51,1±16,5anos); Group 3 18 normal homozygous (WT/WT; 7M/11F, 41,8±15anos). The subjects have done thyroid ultrassonography, avaliation of body composition, thyroid hormones (T3, T4, free T4, TSH), AAM and IGF-I. Statical analysis was made using ANOVA and spearmam correlation index. RESULTS: The group 1 (IGHD) had reduced weight, height, sds h/a, body surface, IGF-I and fat free mass with higher fat mass percent than groups 2 and 3. Group 1 (IGHD) had smaller T3 than group 3 (1,12 ± 0,23 x 1,43 ± 0,2; p < 0,05) (normal control) and higher free T4 than groups 2 (1,2 ± 0,25 x 0,94 ± 0,18; p<0,05) and 3 (1,2 ± 0,25 x 1,01 ± 0,22; p< 0,05) with tendency of higher TSH than group 3. The group 2 had smaller sds h/a (-2,44 ± 1,19 x -1,51 ± 1,2, p<0,05) and IGF-I than group 3 (138,2 ng/ml ± 122,3 x 290,2 ± 160,7; p <0,05). The thyroid volume was smaller in the group 1 (3,59 mL ± 2,09) than group 2 (5,9 mL ± 2,3; p<0,003 ) and 3 (9,24 mL ± 3,12; p<0,0001). The group 2 (heterozygous) had smaller thyroid volume than group 3 (normal homozygous) (p<0,003). When thyroid volume was corrected for body surface, the difference between thyroid volume in groups 1 (3,16 ml ± 1,69) and 2 (3,97 ml ± 1,68) dissapeared. The thyroid volume had positive correlation with IGF-I (r=677; p<0,0001), weight (r= 0,688; p<0,0001), body surface (r=0,678; p=0,000), fat free mass (r=0,717; p<0,0001) e height (r=0,748; p<0,0001) and negative correlation with free T4 (r = -0,278; p < 0,04 )and fat mass percentual (r = -0,631; p < 0,0001) when analysed the total of 46 individuals. When analysed only the IGHD individuals the positive correlation had persisted with fat free mass (r=0,432; p<0,05), height (r=0,489;p<0,02) and body surface (r=0,625; p=<0,02). CONCLUSION: The finding of smaller thyroid volume in GHD and in heterozygous subjects, and its correlation with height and serum IGF-1 indicate a critical role of GH in the determination of the volume of the thyroid gland.